2016
DOI: 10.1371/journal.pntd.0004829
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Suppression of Onchocerciasis Transmission in Bioko Island, Equatorial Guinea

Abstract: Onchocerciasis or "river blindness" is a chronic parasitic neglected tropical disease which is endemic both in mainland and insular Equatorial Guinea. We aim to estimate the current epidemiological situation of onchocerciasis in Bioko Island after vector elimination in 2005 and more than sixteen years of Community Directed Treatment with Ivermectin (CDTI) by using molecular and serological approaches for onchocerciasis diagnosis. A community-based cross-sectional study was carried out in Bioko Island from mid-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Prior to control measures on the island of Bioko, Equatorial Guinea, a survey in the mid 1980s reported that 28.8% of the study population suffered from dermatitis, pigmentation changes and cutaneous atrophy. After vector elimination in 2005 and more than 16 years of CDTi on Bioko Island, a community-based cross-sectional survey was performed in 2014, including a full cutaneous examination [ 67 ]. Although these workers found that 50.4% individuals reported never having taken ivermectin and only 28% had taken it more than twice within the past five years, there was a reduction in pruritus and skin lesions (14.9% complained of pruritus, 3% had nodules, 1.3% had ‘onchodermatitis’ and a further 1.8% had leopard skin.…”
Section: Treatmentmentioning
confidence: 99%
“…Prior to control measures on the island of Bioko, Equatorial Guinea, a survey in the mid 1980s reported that 28.8% of the study population suffered from dermatitis, pigmentation changes and cutaneous atrophy. After vector elimination in 2005 and more than 16 years of CDTi on Bioko Island, a community-based cross-sectional survey was performed in 2014, including a full cutaneous examination [ 67 ]. Although these workers found that 50.4% individuals reported never having taken ivermectin and only 28% had taken it more than twice within the past five years, there was a reduction in pruritus and skin lesions (14.9% complained of pruritus, 3% had nodules, 1.3% had ‘onchodermatitis’ and a further 1.8% had leopard skin.…”
Section: Treatmentmentioning
confidence: 99%
“…This was achieved by a combination of applications by helicopter and ground-based spraying of the organophosphate insecticide temephos that was managed by the WHO African Programme for Onchocerciasis Control (APOC). A follow-up study in early 2014 has shown that no children less than 10 years old have been infected showing that disease elimination is in progress [26].…”
Section: Equatorial Guineamentioning
confidence: 99%
“…volvulus transmission following regular ivermectin distribution to infected individuals and CDTI campaigns in such districts. This is in contrast to the success of ivermectin MDA campaigns to interrupt onchocerciasis transmission and its elimination from a number of countries and certain endemic foci in some countries of Africa and Latin America [ 10 , 21 , 22 , 34 40 ]. However, it could be unrealistic to compare between the successful high-coverage efforts devoted by onchocerciasis elimination programs over a long time in such countries and the low-coverage campaigns implemented by an NGO in the governorates of Tihama.…”
Section: Discussionmentioning
confidence: 91%